C. L. R. James cricket's philosopher king - Renton, Dave. (2007 Haus Publishing, 2007)
Known as 'The Cricketing Marxist', Cyril Lionel Robert James (1901-89) was one of the leading black intellectuals of the 20th century, a Marxist theorist of the first rank, and also one of the finest writers on cricket, with his legendary book Beyond a Boundary. This seeming paradox is reflected in other areas of his life and work: the product of a British-style education and fanatical cricketer who never abandoned the values the sport inculculcated in him, he was a Trotskyite expelled from the USA during the McCarthy era and a friend and inspiration to a generation of leaders of newly-independent African countries such as Kwame Nkrumah of Ghana and Julius Nyerere of Tanzania. Described in his lifetimes as the 'the black Hegel' and 'the black Plato', his book on the 18th century slave revolt in Haiti, The Black Jacobins, is one of great historical works of the 20th century, yet he was never comfortable with the idea of 'Black Studies'. In this fascinating new study of this seminal thinker, Dave Renton hopes to persuade Marxists of the joys of cricket, and followers of cricket of the calibre of James Marxism'
Includes bibliographical references
Keywords: C. L. R. James